The Soledades, Góngora's masque of the imagination - Collins, Marsha Suzan (University of Missouri Press, 2002)
Prince of Darkness or Angel of Light? The pastoral masterpiece the Soledades garnered both titles for its author, Luis de Góngora, one of Spain's premier poets. In The Soledades, Góngora's Masque of the Imagination, Marsha S. Collins focuses on the brilliant seventeenth-century Spanish poet's contentious work of art. The Soledades have sparked controversy since they were first circulated at court in 1612-1614 and continue to do so even now, as Góngora has become for some critics the poster child of postmodernism. These perplexing 2,000-plus line pastoral poems garnered endless debates over the value and meaning of the author's enigmatic, challenging poetry and gave rise to his reputation, causing his very name to become an English term for obscurity. Collins views these controversial poems in a different light, as a literary work that is a product of European court culture. She shows that the Soledades are in essence a court masque, an elaborate theatrical genre that combines a variety of cultural forms and that unfolds in the mind of the reader. Collins maintains that far from serving as an example of "art for art's sake," the Soledades represent Góngora's bid to transform poetic language into a new kind of visionary discourse that allows readers to access secret truths invisible to the average member of the reading public. Each of Collins's four chapters analyzes a different facet of the Soledades, offering readers varied means of approaching Góngora's great work and helping the audience read the poems with greater understanding and appreciation. The Soledades, Góngora's Masque of the Imagination demystifies the daunting, hermetic language of the Soledades to make this masterpiece of imperial Spain accessible to a new, and wider, circle of modern readers. Collins's book transports readers to the court of Habsburg Spain, offering a window to court culture - art, music, alchemy, emblems, garden architecture - and revealing the remarkable beauty of one of Spain's greatest literary masterpieces. Interdisciplinary and cross-cultural in approach, this book will appeal to all Hispanists, including those interested in the current "New Baroque" vogue in Hispanic scholarship, as well as specialists in Renaissance and Baroque English and European literature